The importance of the dissolved organic matter pool for the carbon sequestration potential of artificial upwelling - Gómez-Letona, Markel; Sebastián, Marta; Baños, Isabel; Montero, María Fernanda; Barrancos, Clàudia Pérez; Baumann, Moritz; Riebesell, Ulf; Arístegui, Javier (Frontiers in Marine Science, 2022)
In the face of climate change there is a need to reduce atmospheric CO2 concentrations. Artificial upwelling of nutrient-rich deep waters has been proposed as a method to enhance the biological carbon pump in oligotrophic oceanic regions in order to increase carbon sequestration. Here we examine the effect of different artificial upwelling intensities and modes (single pulse versus recurring pulses) on the dynamics of the dissolved organic matter pool (DOM). We introduced nutrient-rich deep water to large scale mesocosms (~44 m3) in the oligotrophic subtropical North Atlantic and found that artificial upwelling strongly increased DOM concentrations and changed its characteristics. The magnitude of the observed changes was related to the upwelling intensity: more intense treatments led to higher accumulation of dissolved organic carbon (>70 μM of excess DOC over ambient waters for the most intense) and to comparatively stronger changes in DOM characteristics (increased proportions of chromophoric DOM (CDOM) and humic-like fluorescent DOM), suggesting a transformation of the DOM pool at the molecular level. Moreover, the single upwelling pulse resulted in higher CDOM quantities with higher molecular weight than the recurring upwelling mode. Together, our results indicate that under artificial upwelling, large DOM pools may accumulate in the surface ocean without being remineralized in the short-term. Possible reasons for this persistence could be a combination of the molecular diversification of DOM due to microbial reworking, nutrient limitation and reduced metabolic capabilities of the prokaryotic communities within the mesocosms. Our study demonstrates the importance of the DOC pool when assessing the carbon sequestration potential of artificial upwelling.